1986
DOI: 10.1111/j.1600-0536.1986.tb01315.x
|View full text |Cite
|
Sign up to set email alerts
|

Animal model for assessment of skin irritancy

Abstract: Irritant skin reactions from repeated open applications of low concentrations of sodium lauryl sulphate (SLS) have been studied macroscopically and microscopically in guinea pigs. After 3 applications daily for 3 days, 2% SLS aqueous solutions gave a naked eye assessment, increase in epidermal thickness and total dermal inflammatory cell response, which was greater than for a 1% SLS solution. The dermal inflammatory cell response was mainly mononuclear (lymphocytic) in nature. With the SLS reactions as control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…In the literature, histological criteria of qualitative and quantitative evaluation of the cell infiltrate15, 26, 27 as well as the number of basophile cells28 have been used to evaluate allergenic skin reactions. It is further reported that until 48 h after the beginning of the challenge, the number of macrophage and lymphocyte cells diminished, while the number of basophile cells increased 26, 28, 29. An elevated basophile cell count is considered a cutaneous basophile hypersensitivity and represents the weakest form of type IV allergies according to the classification of Coombs and Gell 30.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, histological criteria of qualitative and quantitative evaluation of the cell infiltrate15, 26, 27 as well as the number of basophile cells28 have been used to evaluate allergenic skin reactions. It is further reported that until 48 h after the beginning of the challenge, the number of macrophage and lymphocyte cells diminished, while the number of basophile cells increased 26, 28, 29. An elevated basophile cell count is considered a cutaneous basophile hypersensitivity and represents the weakest form of type IV allergies according to the classification of Coombs and Gell 30.…”
Section: Discussionmentioning
confidence: 99%
“…, One study (Kronevi et al, 1981) in which TCE was applied to the skin of guinea pigs reported the presence of karyopyknosis, karyolysis, spongiosis, and pseudoeosinophilic infiltration in biopsies taken at different times of exposure. Another animal study reported that guinea pigs exhibited considerable erythema, edema, and increased epidermal thickness following an uncovered, dermal exposure to TCE (Anderson et al, 1986). Reports of TCE-induced scleroderma-like illnesses might also have biological plausibility, because sclerotic skin changes can be induced experimentally in mice by exposing them to aliphatic hydrocarbons (Sverdrup, 1984).…”
mentioning
confidence: 96%
“…Mild-to-severe skin irritation was noted in rabbits, guinea pigs, and mice treated topically with mixed xylene (2.3-114 mg/kg/day) in acute studies (Pound and Withers, 1963;Hine and Zuidema, 1970;Consumer Product Testing, 1976;Food and Drug Research Labs, 1976;Anderson et al, 1986). The extent of the irritation appeared to increase with duration of exposure; the most severe dermal irritation ratings were obtained in the longest exposures of 10-days (Hine and Zuidema, 1970).…”
Section: Dermal Exposurementioning
confidence: 99%
“…Limited information is available on the nervous system effects of dermal exposure to xylenes (Goldie, 1960;Hipolito, 1980;Kilbum et al, 1985;Roberts et al, 1988). Acute studies have demonstrated that xylene is irritating to the skin and eyes (Nelson et al, 1943;Wolf et al, 1956;Smyth et al, 1962;Pound and Withers, 1963;Hine and Zuidema, 1970;Carpenter et al, 1975a;Consumer Product Testing, 1976;Food and Drug Research Labs, 1976;Engstrom et al, 1977;Ruhimaki, 1979b;De Ceaurriz et al, 1981;Hake et al, 1981;Klaucke et al, 1982;Nersesian et al, 1985;Anderson et al, 1986). Acute studies have demonstrated that xylene is irritating to the skin and eyes (Nelson et al, 1943;Wolf et al, 1956;Smyth et al, 1962;Pound and Withers, 1963;Hine and Zuidema, 1970;Carpenter et al, 1975a;Consumer Product Testing, 1976;Food and Drug Research Labs, 1976;Engstrom et al, 1977;Ruhimaki, 1979b;De Ceaurriz et al, 1981;Hake et al, 1981;Klaucke et al, 1982;Nersesian et al, 1985;Anderson et al, 1986).…”
Section: Identification Of Data Needsmentioning
confidence: 99%